943. Older Gay Black Men Living with HIV Report Higher Quality of Life than Older Gay White Men, Despite Facing Additional Burdens. (31st December 2020) - Mazonson, Peter; Loo, Theoren; Berko, Jeff; Adeyemi, Oluwatoyin; Oglesby, Alan; Spinelli, Frank; Zolopa, Andrew
Abstract: Background: Improving quality of life (QoL) is an important goal of care for people living with HIV (PLWH). This analysis uses data from the Aging with Dignity, Health, Optimism and Community (ADHOC) online registry to identify the different challenges faced by older white/Caucasian ("white") and black/African American ("black") gay or bisexual men living with HIV, and to assess differences in total QoL between the two groups. Methods: QoL was measured using the PozQoL, a validated instrument for PLWH. The PozQoL assesses QoL across four domains: health concerns, psychological, social, and functional wellbeing. Total QoL was determined by combining domain scores for a total score. Student's t-tests and chi-squared tests were used to identify disparities between black and white men. Factors with p< 0.05 were used as control variables in a multivariable linear regression model where PozQoL total score was the dependent variable. Results: In the ADHOC database, 91% (n=612) of respondents were white men (WM) and 9% (n=59) were black men (BM). Both BM and WM had a median age of 59 years, and had a similar number of comorbidities (7.9 vs 9.2 respectively, p=0.12). Compared to WM, BM were more likely to be single (74% vs 51%, p< 0.001), less likely to have an income greater than 50, 000 (25% vs 56%, p< 0.001), less likely to have a college degree or more (42% vs 69%, p=0.034), and less likely to be virally suppressed (87% vs 96%, p=0.001). Even after controlling for these differences in the multivariable model, BM had significantly higher total QoL than WM (Table 1). Conclusion: In this analysis, there were substantial differences between older BM and WM living with HIV. After controlling for sociodemographic and clinical challenges, BM still reported higher QoL than WM. Programs designed to improve QoL for older gay and bisexual BM and WM living with HIV should take into consideration the unique strengths and challenges faced by each group. Disclosures: Peter Mazonson, MD, MBA, ViiV Healthcare (Grant/Research Support) Theoren Loo, MS, BS, ViiV Healthcare (Grant/Research Support) Jeff Berko, MPH, BS, ViiV Healthcare (Grant/Research Support) Oluwatoyin Adeyemi, MD, ViiV Healthcare (Grant/Research Support) Alan Oglesby, MPH, ViiV Healthcare (Employee) Frank Spinelli, MD, ViiV Healthcare (Employee) Andrew Zolopa, MD, ViiV Healthcare (Employee)